A CASE OF POSTERIOR UVEAL EFFUSION SYNDROME MASQUERADING AS UVEITIS. Issue Volume 11:Issues 1(2017:Winter) (2017) - Liu, Qingyun; Hemarat, Kornwipa; Kayser, Denise L.; Stewart, Jay M.
Abstract : Purpose: To report a case of posterior uveal effusion syndrome presented and treated as posterior uveitis. Methods: We report one case of a 73-year-old woman with posterior uveal effusion syndrome who developed bilateral chorioretinal folds, treated as uveitis, who did not resolve on oral steroids. Results: Nasal choroidal thickening and intraretinal fluid were present in both eyes, along with choroidal folds and yellowish pigmentary changes in the macula. Conclusion: Posterior uveal effusion syndrome can present with features that can mimic uveitis. Abstract : A patient presented with presumed uveitis and was diagnosed with posterior uveal effusion syndrome.